AN APPROACH TOWARDS DEVELOPMENT OF A MIGRATION ENABLED IMPROVED DATACENTER BROKER POLICY - Das, Debashis; Banerjee, Sourav; Kundu, Ayan; Chandra, Swagata; Pal, Saptarshi; Biswas, Utpal (APTIKOM Journal on Computer Science and Information Technologies, 2019)
Cloud computinghas left its remarkable note on the computing world over the last few years. Through itseffectiveness, litheness, scalability & availability cloud computinghas changed the nature of computer systemdeployment. The Quality of Service (QoS) of a cloud service provider (CSP) is an important element of research interestwhich includes different critical issues such as proper load, minimization of waiting time, turnaround time, makespanand suppressing the wastage of bandwidth of the system. The Datacenter Broker (DCB) policy helpsassigning acloudletto a VM. In present study, we proposed an algorithm, i.e., Migration enabled Cloudlet Allocation Policy(MCAP) for allocation of cloudlets to the VMs in a Datacenter by taking into accounttheload capacity of VMs andlength of the cloudlets. The experimental results obtained using CloudSim toolkit under extensive loads that establishperformance supremacy of MCAP algorithm over the existing algorithms.